Pengenalan digital marketing guna mengembangkan UMKM untuk menghadapi pasar global di Desa Cibingbin Kabupaten Kuningan Jawa Barat - Micki Watulandi; Wely Hadigunawan; Rahma Dwi Agustina; Tina Agustina (Abdimas Siliwangi, 2023)
Digitalization is unavoidable at this time. All joints of life in today's society are full of digital touches. So like it or not we have to recognize and play an active role in using digital technology to make the widest use of marketing from villages to cities and even the world. Cibingbin Village has many business actors (MSMEs) in trade. Currently the products produced include dorokdok crackers, emplang crackers, plantation and agricultural fertilizer seeds. Currently the trading system in Cibingbin village is still carried out in a traditional way, namely sellers meet directly with buyers in the market or through direct orders to the place of production. However, the product has not been widely marketed outside the Cibingbin area itself. In community service activities in collaboration with BUMDES, explanations will be provided as well as technical training on increasing product value through digital marketing to recognize product design, product brands, market places, social media, websites, with the methods used in this service, namely presentations, demonstrations and practice. It is hoped that this activity will provide additional insight and new digital marketing methods to prepare for global competition and improve the economic level of MSME business actors in Cibingbin village, Kuningan Regency.Keyword: digital marketing, umkm, community empowerment, BUMDES, market place, social media, website,